PENERAPAN APLIKASI KAHOOT PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN MOTIVASI DAN MINAT BELAJAR SISWA DIKELAS VII SMP NEGERI 38 PADANG - Syelfia Dewimarni; Mishbah Ulhusna; Laila Marhayati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Learning is the main activity of the educational process in schools that aims to produce behavioral changes. These changes include cognitive, affective and psychomotor. This learning activity requires active learning, participation and interactive communication between teachers and students. Learning activities are designed in such a way that they can achieve learning objectives, one of which is learning media. Learning media is designing learning and planning teaching and learning activities. The benefits of learning media clarify the presentation of material and information so as to clarify and improve learning processes and outcomes. This is a challenge for teachers to create fun, interesting and active learning and achieve learning objectives. Against new adaptations that must be accepted in such a way. Learning media that can be used by teachers is Kahoot. Kahoot is an online learning media that contains quizzes and games. Kahoot is also able to help learning evaluation activities become interesting, interactive, conducive and easy to monitor learning outcomes, so that they can provide and increase students' motivation and interest in learning.